'Go Crowded' Advertising Strategy: Increase Travel Agency Intent, Recommendations, and Engagement - Osijo, Immanuel Ustradi; Osiyo, Abraham Krishna Martadinata (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Advertisements play an essential role in shaping consumer intentions and engagement, including in the travel agency industry. The